THEME AND LANGUAGE IN MODERN JAVANESE NOVELS OF THE POST-REFORM ERA - Djoko Sulaksono; Budi Waluyo; Dewi Pangestu Said (Universitas Sebelas Maret, 2017)
Theme is one of the crucial elements of a novel structure because it describes the message conveyed by the author. The description of the theme is closely related to the language used by the author. The readers’ understanding on the theme strogly depends on the language used as a means of delivering messages to the readers. The modern Javanese novels of the post-reform era are assumed to use the Javanese language.